A fast and accurate method to predict reliability of project completion time - Li, Chun-Qing; Zhang, Guomin; Hosseinian, Mahdi (Journal of Civil Engineering and Management, 2017)
To meet the target completion time of a construction project is one of the most important performance indicators of project management. This paper proposes a fast and accurate method for evaluating the reliability of project completion time in large construction projects, using reliability theory. The proposed method is developed to overcome the limitations of existing methods, including the inaccuracy of the program evaluation and review technique and the long computational time of the narrow reliability bounds method. The proposed method is established in three main parts: (i) calculating the statistics of paths duration in the network; (ii) truncating insignificant paths of the network; and (iii) proposing an innovative solution to accurate estimate for reliability of project completion time. The effectiveness of the proposed method is evaluated using an example project. It is found that the results of the proposed method on the reliability of completion time are accurate. It is also found that the proposed method significantly reduces the number of analysed network paths and the computational effort. The method proposed here can serve as a fast and accurate tool for project managers and project planners in project planning, re-planning, and project control phases. First published online: 01 Jul 2016